The Implememtation Of Hiding Information By Using Discrete Wavelet Transform (DWT) - Simbolon, Devi Silvia; Kevin Enrique Keliat; Kristian Sigalingging; Vicky Nainggolan; Rifelson Sipayung (Login : Jurnal Teknologi Komputer, 2024)
Steganography using Discrete Wavelet Transform (DWT) is a technique for embedding information into an image without significantly altering its visual quality. This study aims to analyze the effectiveness of DWT in securing hidden messages within digital images. DWT decomposes image signals into approximation and detail coefficients, allowing data embedding in the high-frequency components while preserving the most essential image features. The research methodology involves converting secret messages into numerical form, applying DWT to the image, embedding data into the detail coefficients, and reconstructing the image using inverse DWT. The results show that this approach enables secure and imperceptible data hiding while maintaining image quality. Additionally, DWT provides advantages in signal analysis, data compression, and noise resistance, making it a robust technique for steganography. The study concludes that DWT is an effective method for secure data embedding with minimal distortion, offering potential applications in digital watermarking and confidential communication.